Horizontal transfer of methoprene and its effect on Tribolium castaneum (Herbst) individuals and populations - Tucker, Angela Marie (Kansas State University, 2012)
Aerosol applications of reduced risk insecticides such as synergized pyrethrin and insect growth regulators (IGR) are part of food industry integrated pest management programs. Since aerosols cannot penetrate into hidden areas exploited by pests such as the red flour beetle, Tribolium castaneum, the potential for these insecticides to effect beetle populations was evaluated. Because IGRs do not cause immediate mortality, the potential of horizontal transfer for an IGR from treated to untreated individuals was also examined. Results showed that when untreated T. castaneum, larvae or pupae, were added to flour containing methoprene, IGR, treated larvae, pupae or adults, the untreated individuals exhibited evidence of methoprene exposure (external deformities and reduced survival). Evaluation of the different mechanisms of transfer indicated that contact with methoprene treated individuals or flour that had been in contact with treated individuals may be the primary method of methoprene transfer. Since aerosols are often applied as a combination of IGR and pyrethrin with a carrier, the effect of these components was evaluated. Applications of synergized pyrethrin caused knockdown of adults but affected adults recovered and progeny production was not effected. Exposure of eggs to these insecticides reduced egg hatch. Food material accumulations inside food facilities can potentially increase or reduce insecticide efficacy. Evaluation of different flour residue levels, representing different sanitation levels, revealed that sanitation alone reduced immature development. As flour residue depths increased more individuals developed into adults but very few developed in the insecticide treatments. Food facilities that use aerosol insecticides apply them at regular intervals, so the cumulative effects of these treatments were considered. Experiments evaluating repeated insecticide exposures indicated that the direct morality from synergized pyrethrin not the horizontal transfer of methoprene was the primary factor in population reduction. Overall findings suggested that methoprene is highly mobile between different surfaces. Exposure of untreated individual beetle larvae to treated larvae or pupae or to flour that has been in contact with exposed beetles can have detrimental effects on development or survival, but these effects may be highly variable and even in cumulative exposures the overall level of population suppression is limited.
Keywords: Tribolium castaneum; Tribolium confusum; Methoprene; Horizontal transfer; Aerosol applications; Agriculture, General (0473); Entomology (0353)